Changes of sperm subpopulations in ejaculates of dogs (Canis lupus familiaris) according to donor age - E. D’Anza; S. Albarella; F. Ciotola; G. Galdiero; R. Pivonello; G. C. Luvoni; V. Peretti (2018)
This study was designed to characterize sperm subpopulations in healthy dogs according to age using morphometric analysis, chromatin fragmentation test and statistical methods. Ejaculates were collected by manual stimulation in one month from 18 healthy master dogs (9 large sized, 7 medium sized and 2 small sized) ranging from 1 to 9 years of age. Seminal parameters as volume, concentration and subjective motility were recorded. Sperm DNA fragmentation was assessed using Sperm-Halomax Kit (Halotech®dna for canine semen) following the manufacturer’s instructions. For morphometric analyses fresh semen was diluted in physiological solution and semen smears were stained with hematoxylin-eosin technique and then observed with a Nikon-Eclipse 80i microscope at 100x magnification. Major axis, minor axis, perimeter, area, shape factor and roughness of 200 spermatozoa/ejaculate were measured with Nis Elements (Nikon) software. All parameters were statistically analysed by IBM SPSS Statistics Version 20. Dogs were ranked into four groups according to age: G1, 1-2 years n= 4; G2, 3–4 years n= 6; G3, 5 years n= 5 and G4, 8 - 9 years n= 3. The ejaculates of each group were classified in five clusters (CLs) as described in (1) using the K-mean algorithm. No significant differences were found among the groups as regard volume, concentration, motility and DNA fragmentation (Kruskal-Wallis test). Pearson correlation test between area and fragmentation values shows an inverse correlation (P<0.01), supposing that to higher mean values of areas they correspond lower fragmentation values. Morphometric parameters were significantly different (P<0.05) among groups (ANOVA test). Clustering evidenced a decrease in the sperm head area over age; in particular morphometric parameters significantly decreased from G1 to G4 (16.38±2.08; 15.84±1.91; 15.42±1.91; 14.13±1.33; P<0.05) so that the number of sperms with small head increased in aged dogs. These data suggest that a decrease of sperm size occurs with aging, but seminal ...